IMPACT OF THE DESTRUCTION OF THE KAKHOVKA RESERVOIR ON THE WATER RESOURCES OF SOUTHERN UKRAINE - SNIZHKO, Sergiy; ZAPOTOTSKYI, Sergii; SHEVCHENKO, Olga; OLEXIENKO, Inna; DIDOVETS, Iulii; BRONSTERT, Axel (Bulletin of Taras Shevchenko National University of Kyiv, Geography, 2023)
Background. The destruction of the Kakhovka hydroelectric power plant dam by the Russian occupiers led to the emptying of the largest reservoir in Ukraine, the Kakhovka reservoir, which provided up to 40% of the water needs of the South of Ukraine. The purpose of the study is to assess the availability of water resources in the South of Ukraine in the context of climate change and the consequences of military actions (destruction of the Kakhovka reservoir by the Russian army). Methods. The research methodology is based on a study of the water balance of the Lower Dnipro River, taking into account the impact of climate change on the region’s water resources based on hydrological modeling of runoff and modern climate projections under two climate scenarios. Results. As a result of the research, an estimate of the availability of water resources in southern Ukraine for the restoration of water infrastructure after the destruction of the reservoir was obtained. It has been established that after the loss of the reservoir, the value of the incoming part of the balance, which is regulated by the inflow of water from the Dnipro reservoir, will not change. However, the amount of water (2.8-4.2 km3 per year) that was spent on evaporation from the reservoir surface and on filtration through the hydroelectric dam will be saved and will be available for use. Another source of replenishment of available water resources is the adjustment of the volume of ecological flow to the Lower Dnipro in winter months by bringing their values closer to natural values (before the construction of the HPP). At the same time, according to the results of the assessment of climate change impacts on the Dnipro water flow in the Kakhovka HPP, in most months of the year under both scenarios (RCP 2.6 and RCP 8.5), a decrease in flow will be observed as a result of climate change. The climatic factor can significantly worsen the water situation in a hydrological year with 50% reliability of water flow in September, and in low-water years with 75% and 95% reliability of water flow from July to November. The largest total deficit of water resources due to climatic and water management factors can be formed in low-water years in September and reach 0.8 km3. Conclusions. Studies conducted to assess the availability of water resources in southern Ukraine after the destruction of the Kakhovka Reservoir have shown that under the influence of further climate change and the resumption of the use of the available water resources of the Dnipro River, water shortages may occur in the summer and autumn, especially in low-water years. However, taking advantage of the artificial regulation of the Dnipro’s flow and the introduction of modern low-water technologies in both industry and agriculture will allow the water sector in southern Ukraine to meet the needs of the water sector without restoring the Kakhovka reservoir.